Resting-state functional reorganization in Parkinson's disease: An activation likelihood estimation meta-analysis. (July 2017) - Tahmasian, Masoud; Eickhoff, Simon B.; Giehl, Kathrin; Schwartz, Frank; Herz, Damian M.; Drzezga, Alexander; van Eimeren, Thilo; Laird, Angela R.; Fox, Peter T.; Khazaie, Habibolah; Zarei, Mojtaba; Eggers, Carsten; et al.
Abstract: Parkinson's disease (PD) is a common progressive neurodegenerative disorder. Studies using resting-state functional magnetic resonance imaging (fMRI) to investigate underlying pathophysiology of motor and non-motor symptoms in PD yielded largely inconsistent results. This quantitative neuroimaging meta-analysis aims to identify consistent abnormal intrinsic functional patterns in PD across studies. We used PubMed to retrieve suitable resting-state studies and stereotactic data were extracted from 28 individual between-group comparisons. Convergence across their findings was tested using the activation likelihood estimation (ALE) approach. We found convergent evidence for intrinsic functional disturbances in bilateral inferior parietal lobule (IPL) and the supramarginal gyrus in PD patients compared to healthy subjects. In follow-up task-based and task-independent functional connectivity (FC) analyses using two independent healthy subject data sets, we found that the regions showing convergent aberrations in PD formed an interconnected network mainly with the default mode network (DMN). Behavioral characterization of these regions using the BrainMap database suggested associated dysfunction of perception and executive processes. Taken together, our findings highlight the role of parietal cortex in the pathophysiology of PD.